2016
DOI: 10.1128/aem.00916-16
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Metagenomic Profiles Have a High Capacity To Discriminate Samples of Activated Sludge According to Wastewater Type

Abstract: This study was conducted to investigate whether functions encoded in the metagenome could improve our ability to understand the link between microbial community structures and functions in activated sludge. By analyzing data sets from six industrial and six municipal wastewater treatment plants (WWTPs), covering different configurations, operational conditions, and geographic regions, we found that wastewater influent composition was an overriding factor shaping the metagenomic composition of the activated slu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 63 publications
(67 reference statements)
5
24
0
Order By: Relevance
“…2). Our other results, that the composition of overall classes was not changed between sampling periods, was also consistent with those by the other conventional techniques (29, 30) (Fig. 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2). Our other results, that the composition of overall classes was not changed between sampling periods, was also consistent with those by the other conventional techniques (29, 30) (Fig. 2).…”
Section: Discussionsupporting
confidence: 90%
“…Until now, most of the microbial research of CAS (18-22, 24-29, 31, 32), and MBR (23, 24, 30) has been focused on the exploration of microbial diversity using the conventional culture-independent molecular techniques with aim to cover almost all the low-abundance microorganisms. These approaches seemed to have targeted such bacterial groups as those that appeared as smeared bands in lower dilutions of DGGE profiles (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sludge sample was collected in a municipal sewage treatment plant located in Argentina [23]. This sample was split in two technical replicates and sequenced with the platform Illumina HiSeq 1500 in 150 bp short reads.…”
Section: Datasets and Platformmentioning
confidence: 99%
“…In either case, the nucleotide sequences of millions of DNA fragments are determined, and then computational analyses are used to identify and quantify all of the organisms (or genes) as long as they are found within already extensive and growing databases (Gilbert and DuPont, 2011;Vanwonterghem et al, 2014). MGA is developing in the academic realm as a powerful approach to gain insight into processes that are of fundamental interest to the WWTP community (Ibarbalz et al, 2016;Jiang, et al, 2016;Sharma et al, 2012;Shchegolkova, 2016;Yang, et al, 2014). Research has shown, for example, that reactor populations can vary over time, at least in part due to changes in climatic and operational conditions (Ju et al, 2014;Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%